2012
DOI: 10.1038/emboj.2012.312
|View full text |Cite
|
Sign up to set email alerts
|

Skin squamous cell carcinoma propagating cells increase with tumour progression and invasiveness

Abstract: Cancer stem cells have been described in various cancers including squamous tumours of the skin by their ability to reform secondary tumours upon transplantation into immunodeficient mice. Here, we used transplantation of limiting dilution of different populations of FACS-isolated tumour cells from four distinct mouse models of squamous skin tumours to investigate the frequency of tumour propagating cells (TPCs) at different stages of tumour progression. We found that benign papillomas, despite growing rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 36 publications
8
86
0
Order By: Relevance
“…1B), suggesting that tumor-initiating cells of WDSCCs, but not those of PD/S-SCCs, retained the ability to differentiate into an epithelial shape. As reported in other mouse models (11,12), a6-integrin It is important to highlight that the tumors that did not progress to PD/S-SCC during serial engraftment did not exhibit an expansion of CSCs or further induction of EMT (OT9 in Supplementary Fig. S2F), indicating that these events are not a consequence of long-term growth in immunodeficient mice.…”
Section: Generation and Characterization Of Lineages Of Skin Scc Progmentioning
confidence: 93%
See 2 more Smart Citations
“…1B), suggesting that tumor-initiating cells of WDSCCs, but not those of PD/S-SCCs, retained the ability to differentiate into an epithelial shape. As reported in other mouse models (11,12), a6-integrin It is important to highlight that the tumors that did not progress to PD/S-SCC during serial engraftment did not exhibit an expansion of CSCs or further induction of EMT (OT9 in Supplementary Fig. S2F), indicating that these events are not a consequence of long-term growth in immunodeficient mice.…”
Section: Generation and Characterization Of Lineages Of Skin Scc Progmentioning
confidence: 93%
“…Wnt/b-catenin, TGFb, and VEGF signaling pathways regulate CD34 þ -CSC features at early stages of progression (11,15,16). Moreover, skin SCC progression is associated with an expansion of the CD34 þ -CSC population (12,16). However, it is not known whether signaling pathways regulating CSC function switch during progression.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Once formed, the growth of SCC is fueled by CSCs (Malanchi et al 2008;Lapouge et al 2011;White et al 2011;Driessens et al 2012) that share several key features of stemness: They can self-renew long-term and differentiate into lineage-restricted progenies of their tissuein this case, the SCC. At the transcriptional level, however, SCC-CSCs differ dramatically from normal skin stem cells, with >700 mRNAs changed by two times or more in CSCs relative to stem cells of either the epidermis or HF (Schober and Fuchs 2011;Lapouge et al 2012).…”
mentioning
confidence: 99%
“…Quantitative PCR (qPCR) analysis of normal skin stem cells and SCC-CSCs purified by fluorescence-activated cell sorting (FACS) (Schober and Fuchs 2011;Lapouge et al 2012) revealed that miR-125b levels in SCC-CSCs were intermediate between epidermal basal progenitors and HFSCs isolated from the bulge niche (Fig. 1B;Schober and Fuchs 2011).…”
mentioning
confidence: 99%